Pride and Social Status - Bolló, Henrietta; Bőthe, Beáta; Tóth-Király, István; Orosz, Gábor (Frontiers in Psychology, 2018)
Pride is a status-related self-conscious emotion. The present study aimed to investigate the nature of status behind pridein four studies with using the two-facet model of pride, status maintenance strategies and with differentiating subjective social status (SSS) and objective social status (OSS). In Study 1 and 2 we used questionnaire methods with structural equation modeling (SEM) in order to identify the relationship patterns between SSS, OSS, status maintenance strategies and pride. In Study 3 and 4 we used vignette methods and SEM to identify these links. All four studies gave evidence for the SSS  prestige status maintenance strategy  authentic pride relationship pattern. Similarly consistent result was found regarding the dominance status maintenance strategy  hubristic pride link. Depending on the assessment method (questionnaire vs. vignette) and the evaluative frame of reference (self vs. other), OSS was related to either authentic and hubristic pride, only hubristic pride, or neither of them. Based on these results, one thing can be taken for granted: pride is a subjective status-related emotion. However, the present results suggest that it is not necessarily true for objective social status.